Tuberculosis of Cervix; a Rare Clinical Entity - Nabi, Uzma; Umber, Fozia; Nafees, Muhammad (International Journal of Pathology, 2018)
Abstract: Tuberculosis of the cervix is a rare disease and accounts for 0.1-0.65% of all cases oftuberculosis and 5-24% of genital tract tuberculosis. We present an unusual case of a 28 years old femalewho presented with chief complaints of lower abdominal pain, irregular bleeding and foul smellingdischarge per vagina for last two years. Cervical examination revealed an unhealthy looking cervixwhich bled on touch. A provisional diagnosis of carcinoma of cervix was made. However,histopathology of the cervical biopsy revealed granulomatous lesion suggestive of tuberculosis. Thepatient responded to anti-tuberculosis therapy. In women with an abnormal cervical appearance, thereshould be high index of suspicious of tuberculosis of cervix, especially from areas where Tuberculosis iscommon as it can be treated easily and successfully.